Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/1527-2648(200203)4:3<125::aid-adem125>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Optimized Anode Functional Layer for Solid Oxide Fuel Cell Applications

Abstract: The main function of the solid oxide fuel cell (SOFC) anode is to provide the reaction sites for the electrochemical oxidation of the fuel gas. Thus, the anode material must be stable in the reducing environment and have sufficient electronic conductivity and catalytic activity for the fuel/gas reaction under operating conditions. A porous cermet made of Ni and yttria-stabilized zirconia (YSZ) is widely used as anode material. The network of Ni particles has a large catalytic activity and is responsible for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…Although thicker anode support layers are desirable in order to assure mechanical strength, these thicker layers decrease the power densities of the cells due to a larger electrode resistance [7]. To overcome these obstacles, the effective use of an anode function layer (AFL) placed between the electrolyte and the anode support has been proposed in literature [8,[11][12][13]. To overcome these obstacles, the effective use of an anode function layer (AFL) placed between the electrolyte and the anode support has been proposed in literature [8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although thicker anode support layers are desirable in order to assure mechanical strength, these thicker layers decrease the power densities of the cells due to a larger electrode resistance [7]. To overcome these obstacles, the effective use of an anode function layer (AFL) placed between the electrolyte and the anode support has been proposed in literature [8,[11][12][13]. To overcome these obstacles, the effective use of an anode function layer (AFL) placed between the electrolyte and the anode support has been proposed in literature [8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted to establish the best film thickness, porosity, and composition for the most part. Hassan et al observed that the rate of leakage of helium gas in leak tests decreases with increasing AFL thickness and stops at a thickness of 16 μm [14]. Kong et al found that a decrease in the thickness of the AFL leads to an increase in the electrical performance of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…SEM (Hassan et al, 2002) Optimizing of AFL Ni, YSZ Both the thickness and the Ni-content of AFL have significant effect to overall cell performance.…”
Section: Advanced 3d Microscopymentioning
confidence: 99%